Efek Sinetron dan FTV dalam Mempengaruhi Pola Pikir Masyarakat - Kurniasari, Nasywa Nurlatifa Riski; Chania, Ramona (Program Studi Ilmu Komunikasi Universitas Negeri Padang, 2023)
Cultivation theory is one of the theories of the effects of mass communication which assumes that continuous exposure to the media in the long run will provide an image and influence on the thoughts and perceptions of the audience. The media here is television. The audience begins to think that what happens in television programs also happens in their lives and reinforces their beliefs about social reality as well as the content on television. One of the television programs that provides an overview and strengthens the audience's beliefs about social reality that is in accordance with television content is soap operas and FTV. This study aims to see the magnitude of the influence of soap operas and FTV on the perspective of people, who watch soap operas and FTV continuously in the long term. This research uses the literature study method. Data collection techniques by paying attention to the responses of soap opera and FTV viewers through social media such as Tiktok comments, comments on Youtube, or seeing responses from interviews on YouTube and previous research journals. The results showed that the audience is quite influentiated, gets other sources of information, ideas, and awareness, which will change perceptions and even behavior if supported by other factors such as individual background or education level.